Estetik dalam Puisi Dunya al-Imam al-Shafi’i - Moktar Hussain; Khazri Osman (International Journal of Islamic Thought, 2017)
Every element in a piece of work, which creates either explicit or implicit, is mutually related to each other. Among the aspects that can be examined to elevate the status of a particular work is the aesthetic value of its language. The early scholars have expertise in all branches of knowledge, however, they still highlight the elements of language in their works. Among the earliest known scholars is al-Imam al-Shafi'i. His authority in the field of fiqh and principals of fiqh is undeniable. However, people did not recognize him as a figure for Arabic literature. Therefore, the current study has to be done to highlight his abilities in terms of Arabic language because of the recognition of many scholars. The study used a qualitative method by making content analysis as a research design. Data collection was done on works that were related to Dunia, then they were analyzed from that aesthetic point of view. The result of this study found that the language style and the interpretation of the Quran and hadith have influenced the uslub (style) and the contents of the poetry of al-Imam al-Shafi'i. In addition, the aspects of balaghah, such as tibaq, jinas, qasr, taqdim, ta'khir, tashbih, in addition to proper selection of words has reinforced the aesthetics in the poems and highlighted the creativity of this great scholar.